PENGARUH BRAND EQUITY DAN ONLINE CONSUMER REVIEW TERHADAP PURCHASE INTENTION PADA PRODUK SUNSCREEN WARDAH - Pramesthya Praba Sari, ida Ayu Gede; Hasbi, Imanuddin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This research is influenced by the problems related to the brand equity and online consumer review on Wardah’s sunscreen products. There are some negative reviews for Wardah sunscreen written by users on the Female Daily and Soco Review websites, when compared to other sunscreen products that already have 2000 more reviews on Female Daily and Soco Review websites, Wardah sunscreen have the lowest score. Compared with other sunscreen products such as Emina, Loreal, and Biore Wardah has the lowest number of sales Shopee and Tokopedia. This study was conducted to determine and anlyze brand equity in Wardah’s sunscreen product, online consumer review in Wardah’s sunscreen product, purchase intention Wardah’s sunscreen product, the influence of the brand equity and online consumer review simultaneously and partially towards purchase intention Wardah’s sunscreen product. This study uses quantitative descriptive research-causality. Sampling technique used was incidental sampling type under non-probability sampling, with the total number of 100 respondents. The data was analysed descriptively, and the hypothesis were tested by using descriptive analysis and multiple linear regression analysis. Based on the results brand equity and online consumer review partially and simultaneously have a significant effect on purchase intention of Wardah’s sunscreen product.